Preparation of New HPLC Stationary Phase and Study of Its Chromatographic Performance Toward the Separation of Some Water-Soluble Vitamins - Abdull-Sattar, Saif S; Maki, Shahbaz A; Ali, Noor M (Al-Nahrain Journal of Science, 2013)
A new stationary phase was prepared by the reaction of a crystal violet solution with silica gel. The capacity of the new prepared resin was calculated and the found average was 6.6meq./g. The resulted resin was highly rigid with high stability and used as stationary phase for HPLC column. Some water-soluble vitamin C, B2, B6, and B12 were examined by this column with isocratic eluention distilled water and methanol (2:98, (v/v)) as a mobile phase with flow rate of 0.5 ml/min and UV detection of 230 nm. The chromatographic performance of the packed column was characterized. The number of plate numbers (N), height equivalent of a theoretical plates (H), capacity factors (K), selectivity factors (α), peaks asymmetry and Resolution (Rs) were measured by analyzing different analytes on the new columns using different mobile phase compositions and flow rates.